Mechanical and Aging Properties of Polypropylene and Styrene-Butadiene-Styrene Composites under Outdoor and Indoor Conditions - Yimit, M.; Ni, L.; Du, Y.; Bkan, R. (Проблемы прочности, 2018)
Polypropylene (PP) and styrene-butadiene-styrene (SBS) blends with different mass fractions were prepared in a molten state using a twin-screw extruder. The effect of SBS content on the microstructure and properties of PP/SBS was discussed by studying the morphology and mechanical properties of PP/SBS outdoor aging samples, using differential scanning calorimeter, universal material testing machine, capillary rheometer, X-ray diffraction and X-ray photoelectron spectrometer. Полипропиленовые и стирол-бутадиен-стирольные смеси с различными массовыми фракциями изготовляли из расплавов с использованием двухшнекового экструдера. Влияние содержания стирол-бутадиен-стирола на микроструктуру и свойства указанных смесей оценивалось путем изучения морфологии и механических свойств образцов, подвергнутых старению во внешней среде, с использованием дифференциального сканирующего калориметра, универсального испытательного стенда и капиллярного реометра, а также методов рентгеновской дифракции и рентгеновской фотоэлектронной спектроскопии.